The Effect of Cylindrical Grip ROM Exercise Therapy on Finger Grip Muscle Strength in The Upper Extremities of Post Stroke Patients - Rizky Meuthia Pratiwi (STIKes Patria Husada Blitar, 2023)
One of the conditions in post-stroke patients is that post-stroke sensory and motor disorders occur on one side of the body, resulting in balance disorders including muscle weakness.Based on a preliminary study conducted in June 2023, it was discovered that 5 respondents who were in the Inpatient Room at Siti Hajar Hospital Sidoarjo most often experienced paralysis in the upper extremities caused by decreased muscle tone so that patients were unable to move their bodies (immobilization). extremity motor abilities through a rehabilitation program.Cylindrical Grip which is a functional hand exercise by holding a cylindrical object such as a glass, bottle, rolled tissue in the palm of the hand (Kleim & Jones, 2008 in Soloman, 2013). The benefits of this therapy are to increase the client's independence and increase muscle strength. Movement exercises can also be useful for improving muscle tone and tendon reflexes.This research used Pre-Experimental design with One Group Pretest and Posttest approach. The population was all post-stroke patients in the inpatient ward who experienced paralysis of the upper right/sinistra extremities at Siti Hajar Hospital. The results of the study proved that there was a change in the value of finger grip muscle strength before and after Cylindrical Grip ROM exercise therapy. The majority of respondents had finger grip muscle strength in the weak category, 23 respondents (76.7%) after being given therapy, different results were obtained, namely the majority of respondents had finger grip muscle strength in the weak category, 15 respondents (50.02). This number decreased after the intervention. Pre and Post data was carried out using the Paired T Test which stated that there was an effect of Cylindrical Grip Exercise Therapy on Finger Grip Muscle Strength in post-stroke patients.